AVALIAÇÃO DE DESEMPENHO DE DOADORAS DA RAÇA PANTANEIRA SUBMETIDAS A OPU/PIVE - ORUÊ, Andrey Makálister Souza; OLIVEIRA, Felipe Gabriel Barbosa de; STERZA, Fabiana de Andrade Melo; SILVA, Aldair félix da; SANTOS, Aracy Garcia Travassos dos; OLIVEIRA, Arianny Lima Ferreira (ANAIS DO ENIC, 2024)
-